EKSTRAK TUMBUHAN SEBAGAI AGEN ANTIMIKROBA UNTUK METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA): REVIEW - Pauzi, Rizqi Yanuar; Septiya, Lia; Ihtiaringtyas, Suci; Wahyudin, Wahyudin (Medical and Health Journal, 2024)
Plant extracts have become an intriguing subject of research in the search for effectiveantimicrobial agents against Methicillin-Resistant Staphylococcus Aureus (MRSA), which is a global health issue due to its resistance to various antibiotics. Several studies have shown that compounds such as alkaloids and polyphenols in plants are responsible for their antimicrobial properties. Extracts from plants such as Azadirachta indica, Psidium guajava, and Rhamnus californica have demonstrated antibacterial activity against MRSA. Other research indicates that compounds like Psorothatin C from Psorothamnus fremontii are also effective against MRSA. The main challenge in managing MRSA infections is resistance to conventional antibiotics like vancomycin. Therefore, further research on plant extracts and synthetic compounds with antimicrobial activity against MRSA could provide significant contributions to the development of new therapies. Approaches involving the combination of plant extracts with conventional antibiotics also show potential in enhancing treatment effectiveness. A deep understanding of the mechanisms of action of these plant extracts is crucial for developing effective treatment strategies, and with further research, plant extracts could become an important alternative in addressing MRSA infections that are resistant to antibiotics.